Slippery discourses of intertwined crises: migration and Covid-19 pandemic in a postcolonial nation - Minga, Ester (MedieKultur: Journal of media and communication research, 2024)
The outbreak of a pandemic inevitably links with migration as containment measures usually involve the closure of borders. In the Portuguese context, mediated discourses of these intertwined crises were varied and multifaceted, reflecting the country’s postcolonial peculiarity as both a provider of emigrants and host country to distinct fluxes of migrants. Through a qualitative analysis of selected items published in Portuguese newspapers Expresso, Diário de Notícias, and Correio da Manhã, I will show how similar issues involving Portuguese emigrants and distinct groups of migrants have been differently framed in news items related to the Covid-19 pandemic. The aim is to discuss how this unstable coverage speaks to, and collides with, the deep social imaginary of Portuguese emigration and the widespread idea of a Lusophone space characterized by the harmonious conviviality of different people. I argue that the fragmented frames represent a symptom of crisis themselves, revealing unsettled discourses and alternating anxieties.